(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The systems containing 0,4-0,6 mmol/g of active bromine on activated carbon surface were obtained by original bromination methods. It was show that such Br may be easily substituted by sulfur and further hydrolyzed and oxidized to produced SO3H-groups (up to 0,25 mmol/g). It was established by TGA and TPD-IR methods that obtained systems are thermaly stable –is characterized by maximum of SO2 desopbtion at 250-300°C and 350-390°C. These systems show medium catalytic activity in isopropanol dehydration. Temperature of 90 % isopropanol conversion is 240-275°C.